Effects of Water Replenishment from Yellow River on Water Quality of Hengshui Lake Wetland - Xu, Weigang; Yu, Yilei; Ma, Muyuan; Guo, Jia; Zhao, Nana; Li, Xiaoxia (Journal of Plant and Animal Ecology, 2018)
Hengshui Lake Wetland is the only national wetland and bird nature reserve in the North China Plain. It plays an important role in maintaining the species diversity and ecological balance. In recent years, due to industrial and agricultural production, infrastructure and ecological environment construction and other reasons, the infiltration, runoff, evapotranspiration and other water balance elements was changed, which reduced runoff into the lake. In order to ease the tense water resources situation in the region, Hengshui Lake is replenished each year by Yellow River water. Although Diversion Yellow River Wetland has made direct water supply protection, but also affected the ecology and environment of Hengshui Lake wetlands. In order to understand how artificial water diversion can affect the ecological environment of natural lakes, this paper analyzes the effects of artificial water storage on the water quality of the lake by using the measured data of water samples in the lake. The results showed that the water level of Hengshui Lake showed an upward trend after the diversion from the Yellow River. Comprehensive pollution index showed a downward trend, but Hengshui Lake wetlands are still slightly polluted. Diversion of Yellow River diversion into the lake of the ecological health of Hengshui also caused some impact.
Keywords: Hengshui Lake wetlands